2012
DOI: 10.4238/2012.june.27.5
|View full text |Cite
|
Sign up to set email alerts
|

RAPD analysis of genetic diversity and population structure of Elymus sibiricus (Poaceae) native to the southeastern Qinghai-Tibet Plateau, China

Abstract: ABSTRACT. Genetic diversity of Elymus sibiricus (Poaceae) was examined in eight populations from the southeast Qinghai-Tibet Plateau. We detected 291 RAPD polymorphic loci in 93 samples. The percentage of polymorphic bands (PPB) was 79%. Genetic diversity (H E ) was 0.264, effective number of alleles (N E ) was populations per generation (N m ) was 1.06. The populations were found to share high levels of genetic identity. No significant correlation was found between geographic distance and pairwise genetic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…The average band per primer was 10.8. The percentage of polymorphic bands (91.91%) was higher than the PPB values previous studies of SRAP variation (PPB = 86.48%) [ 6 ], SSR variation (PPB = 86.88%) [ 20 ], ISSR variation (PPB = 77.20%) [ 5 ], and RAPD variation (PPB = 78.65%) [ 21 ]. Previous studies showed that environment parameters are highly correlated with the magnitude and distribution of genetic diversity [ 5 , 8 ].…”
Section: Resultsmentioning
confidence: 62%
“…The average band per primer was 10.8. The percentage of polymorphic bands (91.91%) was higher than the PPB values previous studies of SRAP variation (PPB = 86.48%) [ 6 ], SSR variation (PPB = 86.88%) [ 20 ], ISSR variation (PPB = 77.20%) [ 5 ], and RAPD variation (PPB = 78.65%) [ 21 ]. Previous studies showed that environment parameters are highly correlated with the magnitude and distribution of genetic diversity [ 5 , 8 ].…”
Section: Resultsmentioning
confidence: 62%
“…For example, a number of studies have been conducted on the genetic diversity of E. caninus [25,26], E. fibrosus [27][28][29], E. alaskanus [30][31][32][33], E. trachycaulus [34,35], and E. sibiricus [36,37]. These studies have shown that each species possesses a unique pattern of genetic variability, and they are useful for understanding the genetic diversity for similar outcrossing grass species.…”
Section: Introductionmentioning
confidence: 99%
“…Elymus sibiricus (Siberian wildrye) is a perennial, caespitose grass, widely distributed around the world (Ma et al, 2012 ). It usually grows on arid or semiarid mountain or valley grasslands at altitudes from 1,000 to 4,000 m in northwestern China.…”
Section: Introductionmentioning
confidence: 99%
“…It usually grows on arid or semiarid mountain or valley grasslands at altitudes from 1,000 to 4,000 m in northwestern China. It has also played an important role in native grassland restoration on the Qinghai-Tibet Plateau of China as a pioneer grass species (Ma et al, 2012 ). E. sibiricus usually serves as an important forage grass, and has been widely employed in establishing sown grasslands to develop stock raising, due to its strong adaptability, excellent tolerance to drought and cold, high crude protein content, and good palatability (Yan et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%